Controlling of crystal size and optical band gap of CdO nanopowder semiconductors by low and high Fe contents - Aydın, Cihat; Al- Hartomy, Omar A.; Al- Ghamdi, A. A.; Al- Hazmi, F.; Yahia, I. S.; El- Tantawy, F.; Yakuphanoğlu, Fahrettin (My University, 2012)
The CdO:Fe nanopowder semiconductors were synthesized by the sol–gel calcination for the first time. The structural properties of Fe doped CdO samples were analyzed by AFM and XRD measurements. XRD patterns of the pure and Fe-doped CdO samples reveal that the pure and Fe doped CdO nanopowders are polycrystalline of cubic CdO structure. The crystallite size of undoped and Fe-doped CdO samples is changed unsystematically with a regular increase of Fe content. The optical band gaps of Fe doped CdO samples were determined for the first time by diffused reflectance measurements. The optical band gap of the samples is increased with the increase of Fe dopant inside the host matrix (CdO) up to 15 % followed by a decrease in its value. It is evaluated that Fe doped CdO nanopowder semiconductors can be producted by sol–gel calcination for advanced technological applications
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: CdO:Fe; Nanopowders; Sol gel; Optical properties; Diffused reflectance